(untitled) (Scientific journal of the Fergana State University, 2025)
The article describes the factors influencing the formation of soils in the cities of Fergana and Kokand, the processes of urban pedogenesis, the specifics of the classification of urban soils, their morphological structure, physicochemical properties, as well as their differences from natural analogues. Soils and earthy wounds of the city and adjacent areas are formed under the strong influence of the anthropogenic factor. In the process of Urban Construction, a large number of kotlovans , trenches are dug, water, sewage, an earthen cover with abandoned underground roads are pushed, taken away, mixed with various gurunts, sometimes used as a building material. They will be replaced by a large amount of construction and household waste. They are usually leveled, and not brought grunts are laid on top. Asphalt and concrete coverings are laid over a large part of the urban area. Natural plants alternate with urbophytocenosis. The soil will not be able to cope with the tasks to be performed, including environmental ones. Industrial enterprises, transport as well as household disposal and waste pollute soils with heavy metals and other chemical compounds. These processes ultimately affect human health.